2023
DOI: 10.1039/d2sc05789a
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Suzuki cross-coupling of 1,2-diboryl cyclopropanes

Abstract: Herein, we describe the catalytic enantioselective cross-coupling of 1,2-bisboronic esters. Prior work on group specific cross coupling is limited to the use of geminal bis-boronates. This desymmetrization provides a novel...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…In contrast to primary organoboron reagents, secondary coupling partners are significantly less reactive in non-radical-based Suzuki cross-coupling, such that couplings of these more hindered substrates often suffer from chain-walking due to β-hydride elimination processes. , Indeed, other than recent systems developed by Burke and by Biscoe and Sigman, secondary boronate cross-couplings have relied upon inherently reactive substrates (cyclopropyl, benzylic, allylic, or those with directing groups) for effective reaction. Recent studies in our laboratory revealed that aliphatic 1,2-bis­(boronic esters) ( 1 , Figure b) are remarkably reactive substrates in Suzuki–Miyaura reactions with the presence of an adjacent organoboronate providing >50-fold rate acceleration in Pd-catalyzed cross-coupling . More recent experiments involving copper catalysis revealed similar substrate activation, with the origin of rate enhancement being traced to the intermediacy of a strained cyclic chelated ate complex (i.e., 4 , Figure b) .…”
mentioning
confidence: 88%
“…In contrast to primary organoboron reagents, secondary coupling partners are significantly less reactive in non-radical-based Suzuki cross-coupling, such that couplings of these more hindered substrates often suffer from chain-walking due to β-hydride elimination processes. , Indeed, other than recent systems developed by Burke and by Biscoe and Sigman, secondary boronate cross-couplings have relied upon inherently reactive substrates (cyclopropyl, benzylic, allylic, or those with directing groups) for effective reaction. Recent studies in our laboratory revealed that aliphatic 1,2-bis­(boronic esters) ( 1 , Figure b) are remarkably reactive substrates in Suzuki–Miyaura reactions with the presence of an adjacent organoboronate providing >50-fold rate acceleration in Pd-catalyzed cross-coupling . More recent experiments involving copper catalysis revealed similar substrate activation, with the origin of rate enhancement being traced to the intermediacy of a strained cyclic chelated ate complex (i.e., 4 , Figure b) .…”
mentioning
confidence: 88%
“…Due to our interest in the development of enantioselective strategies for the synthesis of strained, conformationally rigid hydrocarbons as medicinal chemistry-relevant structures, [47][48][49][50][51] we wondered if it would be possible to establish a convenient preparation of enantioenriched 1,5-disubstituted bicyclo[2.1.1]hexanes. From the outset, we aimed to prepare bifunctional building blocks with two versatile and highly modulable handles that would allow easy incorporation into drug analogues.…”
Section: Designmentioning
confidence: 99%
“…We thought this to be a viable route because of previous work done that demonstrates alkyl boronic esters can undergo cross-coupling chemistry. [11][12][13][14][15][16][17][18][19][20] Herein, we report a new methodology to control the regioselectivity of 2,3-diarylpropionic acids by utilizing a copper-catalyzed boracarboxylation followed by a Suzuki-Miyaura cross-coupling to various aryl halides.…”
Section: Introductionmentioning
confidence: 99%